Crystallizer casting powder capable of reducing corner cracks, medium carbon steel plate blank and preparation method of medium carbon steel plate blank

By using a specific composition of crystallizer to protect slag and optimized crystallizer vibration curve and cooling water volume control in the production of medium carbon steel, the problem of corner cracks in the medium carbon steel slab is solved, and the product quality and production efficiency are significantly improved.

CN119657858APending Publication Date: 2025-03-21HUNAN IRON & STEEL GRP TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671297.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Medium carbon steel often has corner cracks during the production process, affecting the normal production and product quality.

Method used

A specific crystallizer protection slag is used, including a specific proportion of SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Li2O, Na2O, MnO, H2O, F and C, combined with the optimized crystallizer vibration curve and cooling water volume control, to reduce the corner cracks of the medium carbon steel slab.

Benefits of technology

It effectively reduces the angle cracks of medium carbon steel, improves the surface quality of the cast billet, reduces the loss rate of flame cleaning, and reduces the one-rolling and reworking of the steel coil after hot rolling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657858A_ABST
    Figure CN119657858A_ABST
Patent Text Reader

Abstract

The invention discloses crystallizer casting powder capable of reducing corner cracks, a medium carbon steel plate blank and a preparation method of the medium carbon steel plate blank, and relates to the field of steel material preparation. The preparation method comprises the steps that medium carbon steel raw materials are smelted into molten steel, conventional slab casting is conducted, the alkalinity of crystallizer casting powder is high, heat transfer can be relieved, a sinusoidal vibration curve of a crystallizer is controlled so as to reduce the vibration mark depth and the vibration mark interval, weak cooling can be achieved by controlling the cooling water flow of the crystallizer, and the molten steel is gradually solidified into a blank in the crystallizer; according to the method, the growth uniformity of a blank shell is ensured, the crack tendency of a casting blank is weakened, the corner crack probability of the prepared plate blank is obviously reduced, the surface quality of the plate blank is greatly improved, the loss rate of flame cleaning is effectively reduced, the quality condition of a steel coil subjected to follow-up hot rolling machining is tracked, and the conditions of descending, repairing and the like after the steel coil is rolled are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of steel material preparation, and in particular to a mold protection slag for reducing corner cracks and a medium carbon steel slab and a preparation method thereof. Background Art

[0002] The designed C content of medium carbon steel is generally between 0.16 and 0.19. The production of medium carbon steel in the 210 converter plant is about 200,000 tons per month. However, when producing medium carbon steel, such as Q345XJ-H, A36-LB, Q235B and other steel grades, there are basically corner cracks, and the corner cracks mostly appear close to the inner arc corner of the slab, and almost all occur at the bottom of the vibration mark, causing great trouble to the normal production.

[0003] Research has found that the main reason for the cracks in the corners of medium carbon steel is that the slab in the fan-shaped segment is in contact with secondary cooling water during the solidification, bending and straightening process. The function of the secondary cooling water is to absorb the heat of the slab and promote the solidification of the molten steel into a slab. Since the corners of the slab are cooled in two dimensions, the corner temperature is lower than other positions. When pouring medium carbon steel with strong crack sensitivity, due to the low corner temperature of the slab, cracks will appear at the inner arc corners of the slab during the straightening process, and warping defects will appear at the edge of the steel coil during rolling, affecting customer use. It is necessary to find a preparation process that can effectively reduce the cracks in the corners of medium carbon steel. Summary of the invention

[0004] The present invention provides a mold protection slag and a medium carbon steel slab for reducing corner cracks and a preparation method thereof. When conventional slabs are used to cast medium carbon steel, the corner cracks of the medium carbon steel can be effectively reduced, the surface quality of the medium carbon steel ingot is greatly improved, and the downgrading rate, the rework rate and the loss rate of flame cleaning are effectively reduced.

[0005] In order to solve the above technical problems, one of the objectives of the present invention is to provide a crystallizer protection slag for reducing corner cracks of medium carbon steel slabs, comprising the following components by mass fraction: 30.05wt%-32.5wt% SiO2, 5.35wt%-5.55wt% Al2O3, 1.07wt%-0.87wt% Fe2O3, 37.39wt%-39.39wt% CaO, 4.21wt%-4.41wt% MgO, 0.16wt%-0.18wt% K2O, 0.7wt%-0.9wt% Li2O, 5.3wt%-5.5wt% Na2O, 0.02wt%-0.04wt% MnO, 1.52wt%-1.72wt% H2O, 7.96wt%-8.16wt% F, 4.55wt%-4.75wt% C.

[0006] By adopting the above scheme, the alkalinity of the crystallizer protective slag of the present application can be slightly increased, which is beneficial to the formation of a crystalline phase in the solid slag film, the interface thermal resistance is increased, the glass body is reduced, and the radiation heat transfer is reduced, thereby achieving the purpose of slowing down the heat transfer. For conventional slab casting of medium carbon steel, it can effectively reduce the corner cracks of medium carbon steel, and at the same time avoid the alkalinity being too high to cause the liquid slag film thickness to decrease and affect the lubrication of the ingot. In addition, in order to avoid poor lubrication of the ingot due to increased alkalinity, the present application reduces the viscosity of the protective slag to ensure the lubrication of the ingot and prevent the ingot from sticking or leaking. Due to the reduction in viscosity, the slag consumption increases accordingly. Therefore, the melting rate of the protective slag is increased to ensure the slag consumption, thereby comprehensively improving the product quality.

[0007] As a preferred solution, the basicity of the mold protection slag is 1.17-1.37, and the melting rate at 1350°C is 26-28 kg / (m 2 ·s), and the viscosity at 1300℃ is 0.113-0.133Pa·s.

[0008] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing a mold protection slag for reducing corner cracks of a medium carbon steel slab, comprising the following steps:

[0009] (1) weighing the raw materials of each component according to the ratio, mixing them evenly, adding water to the raw materials to mix, the mass ratio of the raw materials to water is 1:(1-2), wet grinding, and then sieving, the mesh size of the sieve is 0.1-1 mm, to obtain a slurry;

[0010] (2) forming a granular protective slag by spray granulation;

[0011] (3) Drying and screening the granular protective slag to obtain a finished product of the crystallizer protective slag, the drying temperature is 100-150° C., the drying time is 2-8 hours, and the particle size of the finished product of the crystallizer protective slag is 0.1-1 mm.

[0012] In order to solve the above technical problems, the third object of the present invention is to provide a method for preparing a medium carbon steel slab with reduced corner cracks, comprising the following steps:

[0013] The medium carbon steel raw material is melted into molten steel, and the large ladle of molten steel is injected into the tundish through the long nozzle. The molten steel in the tundish flows into the crystallizer through the integral immersion nozzle. The crystallizer protective slag is added in advance to control the sinusoidal vibration curve of the crystallizer to be S=1+2V c , f=170-20V c , where S: stroke, mm; f: vibration frequency, min -1 ; V c: Pulling speed, m / min, control the cooling water volume of the wide surface of the crystallizer to 3900-4100L / min, and the cooling water volume of the narrow surface of the crystallizer to 370-390L / min. The molten steel gradually solidifies into a billet in the crystallizer, and then immerses it in the secondary cooling section for cooling to obtain a medium carbon steel slab.

[0014] By adopting the above scheme, the sinusoidal vibration curve of the crystallizer in the carbon steel continuous casting process in this application is controlled to be S=2+2V c , f=170-2V c , which makes the negative sliding, positive sliding time and oscillation mark spacing all lower. Reducing the negative sliding time can reduce the depth of the oscillation mark. The reduction in the oscillation mark depth and the oscillation mark spacing are both helpful to reduce the transverse crack defects at the corners of the ingot; at the same time, in order to reduce the shrinkage of the ingot shell and ensure the uniform growth of the ingot shell thickness, the present application controls the cooling water volume of the wide surface of the crystallizer to 3900-4100L / min, and the cooling water volume of the narrow surface to 370-390L / min, to achieve weak cooling, ensure the uniformity of the ingot shell growth, and weaken the crack tendency of the ingot. Ultimately, the probability of cracks at the corners of the prepared slab is significantly reduced, the surface quality of the slab is greatly improved, the loss rate of flame cleaning is effectively reduced, and the quality of the steel coils processed by subsequent hot rolling is tracked. It is found that the downgrading and rework of the steel coils after rolling are reduced.

[0015] As a preferred embodiment, the drawing speed of the casting machine in the crystallizer is 0.9-1.5 m / min.

[0016] As a preferred embodiment, the negative sliding time of the crystallizer is 0.1540-0.1543s.

[0017] As a preferred solution, the medium carbon steel grade is any one of Q235B, Q345XJ-H, A36-LB, CCS-A, and SS400.

[0018] As a preferred solution, the dimensions of the crystallizer are 200-250 mm in thickness, 850-950 mm in length, and 1200-1300 mm in width.

[0019] As a preferred solution, the inlet temperature of the crystallizer cooling water is 22-28°C.

[0020] In order to solve the above technical problems, a fourth object of the present invention is to provide a medium carbon steel slab with reduced corner cracks.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. For conventional slab casting of medium carbon steel, the present application controls the mold protective slag to have a higher basicity, which is beneficial to the formation of a crystalline phase in the solid slag film, thereby achieving the purpose of slowing down heat transfer and helping to reduce corner cracks of medium carbon steel. At the same time, the present application reduces the viscosity of the protective slag to ensure the lubrication of the ingot, prevents the ingot from sticking or leaking, increases the melting rate of the protective slag to ensure the slag consumption, and comprehensively improves product quality.

[0023] 2. In this application, the sinusoidal vibration curve of the control mold during the carbon steel continuous casting process is S=2+2V c , f=170-2V c , which makes the negative sliding, positive sliding time and oscillation mark spacing all lower. Reducing the negative sliding time can reduce the depth of the oscillation mark. The reduction in the oscillation mark depth and the oscillation mark spacing are both helpful to reduce the transverse crack defects at the corners of the ingot. By tracking the quality of the steel coils processed by subsequent hot rolling, it was found that the downgrading and rework of the steel coils after rolling were reduced.

[0024] 3. In order to reduce the shrinkage of the billet shell and ensure uniform growth of the billet shell thickness during conventional slab casting of medium carbon steel, the present application controls the cooling water flow on the wide surface of the crystallizer to achieve weak cooling and reduce the tendency of cracks in the cast billet, which helps to reduce the probability of cracks in the corners of the slab, greatly improves the surface quality of the slab, effectively reduces the loss rate of flame cleaning, and tracks the quality of steel coils processed by subsequent hot rolling. It is found that the downgrading and rework of the steel coils after rolling are reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : A photograph of the corner of a medium carbon steel slab with reduced corner cracks in Example 1 of the present invention;

[0026] Figure 2 : A photograph of the corner of a medium carbon steel slab in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The following Table 1 shows the sources and types of raw materials used in the examples and comparative examples of the present application. Unless otherwise specified, the raw materials used can be obtained commercially, and the same raw materials are used in parallel experiments.

[0029] Optimization of crystallizer vibration curve: The sinusoidal vibration used before the continuous casting machine optimization is as follows: S = 1.5 + 2V c , f=120-2Vc ; S: stroke, mm; f: vibration frequency, min -1 ; V c : Casting speed, m / min; Through analysis, it was found that the original negative sliding time was too high, so the vibration of the continuous casting machine was adjusted to increase the vibration frequency and reduce the amplitude. The optimized adjustment of sinusoidal vibration is as follows: S = 2 + 2V c , f=170-2V c , the calculation related parameters are shown in Table 1.

[0030] Table 1-Continuous Casting Machine Vibration Process Parameters

[0031]

[0032]

[0033] By comparing Table 1, it can be seen that after adjusting the crystallizer vibration curve, the stroke is reduced by 1mm, the pulling speed is from 0.9m / min to 1.1m / min, the vibration frequency is increased by 55.9%, 56.9%, 57.9% and 60.0% respectively, and the displacement difference under different typical pulling speeds increases by 10.9%-27.9%, while the negative sliding time is reduced by about 32%, and the positive sliding time is reduced by about 40% when the pulling speed is 0.9-1.0m / min after adjustment, and the positive sliding time is reduced to 73.0% when the pulling speed is 1.1m / min, and the time ratio is slightly increased, with a small amplitude. Due to the significant reduction in negative sliding time, the depth of the vibration mark can be significantly reduced in theory. The vibration mark spacing is reduced by 3.31-3.86mm according to the calculation formula of the slab vibration mark. The reduction in the vibration mark depth and the reduction in the vibration mark spacing are both important for reducing the transverse crack defects at the corners of the casting.

[0034] The calculation formula for the slab vibration mark is: p=Vc / f; wherein p is the vibration mark spacing, unit is m; Vc is the billet drawing speed, unit is m / s; F is the vibration frequency of the crystallizer, unit is Hz.

[0035] Preparation Example 1

[0036] A crystallizer protective slag, comprising 30.15wt% SiO2, 5.45wt% Al2O3, 0.97wt% Fe2O3, 38.39wt% CaO, 4.31wt% MgO, 0.17wt% K2O, 0.8wt% Li2O, 5.4wt% Na2O, 0.03wt% MnO, 1.62wt% H2O, 8.06wt% F, 4.65wt% C 自由 , comprising the following preparation steps:

[0037] (1) Weigh the raw materials of each component according to the ratio and mix the raw materials evenly;

[0038] (2) adding water to the raw materials, mixing them in a raw material to water mass ratio of 1:1, wet grinding, and then sieving with a sieve mesh size of 0.5 mm to obtain a slurry;

[0039] (3) The slurry is formed into granular protective slag by spray granulation, and the granular protective slag is dried and sieved at a drying temperature of 120° C. and a drying time of 6 hours to obtain a finished crystallizer protective slag. The particle size of the finished crystallizer protective slag is 0.5 mm.

[0040] Example 1

[0041] A medium carbon steel slab with reduced corner cracks, the preparation method of which comprises the following steps:

[0042] (1) The casting steel grade is Q235B, with a C content of 0.18%, a casting length of 15 furnaces, and a continuous casting machine roll gap within the standard requirements ( + 1mm), nozzle: no blockage in 0-3 sections; total blockage number in 4-8 sections is 4, ≤5, the SEN nozzle is measured for centering when pouring, the inner and outer arc deviation is 1.5mm, ≤2mm, and the two-stream pulling speed is controlled at 1.4m / min;

[0043] (2) The molten steel of the large ladle of Q235B steel grade is injected into the tundish through the long nozzle, and argon gas is used for protection. The molten steel in the tundish flows into the crystallizer through the integral immersion nozzle. The protective slag obtained in Preparation Example 1 is added to the crystallizer. The dummy rod is used to block the bottom of the crystallizer. The casting machine and the crystallizer vibration device are started, and the sinusoidal vibration curve of the crystallizer is controlled to be S=1+2V c , f=170-20V c , S: stroke, mm; f: vibration frequency, min -1 ; V c : Pulling speed, m / min, the pulling speed is 1.4m / min, the size of the crystallizer is 230mm thick, 900mm long, and 1250mm wide, the cooling water volume on the wide side of the crystallizer is controlled to be 4000L / min, the water volume on the narrow side of the crystallizer is set to 380L / min, the cooling water inlet temperature is 25℃, the molten steel gradually solidifies into a blank in the crystallizer, and then immerses it in the secondary cooling section for water spray cooling to obtain a medium carbon steel slab. There is no corner crack at the corner of the medium carbon steel slab. Figure 1 As shown, the specifications of the continuous casting billet are 240mm×1500mm.

[0044] Example 2

[0045] A medium carbon steel slab with reduced corner cracks, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), the casting steel type selected is Q345XJ-H.

[0046] Example 3

[0047] A medium carbon steel slab with reduced corner cracks, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), the casting steel type selected is A36-LB.

[0048] Example 4

[0049] A medium carbon steel slab with reduced corner cracks, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), the casting steel type selected is CCS-A.

[0050] Example 5

[0051] A medium carbon steel slab with reduced corner cracks, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), SS400 is selected as the casting steel type.

[0052] Comparative Example 1

[0053] A medium carbon steel slab, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), the cooling water volume on the wide surface of the crystallizer is controlled to be 4200 L / min, and the water volume on the narrow surface of the crystallizer is set to 400 L / min.

[0054] Comparative Example 2

[0055] A medium carbon steel slab, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), the cooling water volume on the wide side of the crystallizer is controlled to be 3800 L / min, and the water volume on the narrow side of the crystallizer is set to 360 L / min.

[0056] Comparative Example 3

[0057] A medium carbon steel slab, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), the cooling water volume on the wide surface of the crystallizer is controlled to be 3600 L / min, and the water volume on the narrow surface of the crystallizer is set to 340 L / min.

[0058] Comparative Example 4

[0059] A medium carbon steel slab, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), the crystallizer protective slag is Kefeng medium carbon protective slag, model number KFB-medium carbon.

[0060] Comparative Example 5

[0061] A medium carbon steel slab, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), the sinusoidal vibration curve of the crystallizer is controlled to be S=1.5+2V c , f=120-25V c , S: stroke, mm; f: vibration frequency, min -1 ; V c : Pulling speed, m / min.

[0062] Comparative Example 6

[0063] A medium carbon steel slab, wherein each step of the preparation method and the materials, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), the mold protection slag is Kefeng medium carbon protection slag, model KFB-medium carbon, the cooling water volume of the wide surface of the crystallizer is controlled to be 4200 L / min, and the water volume of the narrow surface of the crystallizer is set to 400 L / min, and the corner cracks of the obtained medium carbon steel slab are as follows Figure 2 shown.

[0064] Production performance test

[0065] 1. The basicity R value, melting point, melting rate at 1350°C, and viscosity at 1300°C of the mold protection slag of Example 1 and Comparative Example 4 were measured. The measurement results are shown in Table 2 below.

[0066] Table 2 - Performance test results of the mold protection slag of Example 1 and Comparative Example 4 of the present application

[0067]

[0068] 2. The medium carbon steel slabs prepared in the embodiment and the comparative example were pickled, and the slabs were immersed in a 5wt% hydrochloric acid solution for 5 minutes, washed with water, and then observed whether there were cracks at the corners of the slabs. The probability of corner cracks in 1000 batches of production samples was counted, and the statistical results are shown in Table 3 below.

[0069] 3. The medium carbon steel slabs prepared in the embodiment and the comparative example were subjected to subsequent hot rolling to verify the processing performance, including slab heating, rough descaling, rough rolling, fine descaling, fine rolling, layer cooling, coiling, and bulk storage steps. The surface of the steel coil samples after hot rolling was observed for pitting peeling, and the probability of pitting peeling of 1000 batches of production samples was counted. The statistical results are shown in Table 3 below.

[0070] Table 3 - Products and processing performance results of medium carbon steel slabs prepared in the present examples and comparative examples

[0071]

[0072]

[0073] As shown in Table 3, in Comparative Examples 1-3, the cooling water volume of the wide surface of the crystallizer was controlled to be 4200 L / min, 3800 L / min, and 3600 L / min, respectively, and the water volume of the narrow surface of the crystallizer was set to 400 L / min, 360 L / min, and 340 L / min, respectively. The minimum shell thickness of the ingot in Comparative Example 3 was 16.6 mm, reaching the lower limit of the theoretical value. However, the probability of corner cracks in the slabs prepared in Comparative Examples 1-3 was relatively high. In Example 1, in order to reduce the shrinkage of the shell and ensure uniform growth of the shell thickness, the cooling water volume of the wide surface of the crystallizer was controlled to be 4000 L / min, and the cooling water volume of the narrow surface was 380 L / min, so as to achieve weak cooling, ensure uniform growth of the shell, and weaken the crack tendency of the ingot. The probability of corner cracks in the prepared slab was significantly reduced, the surface quality of the slab was greatly improved, and the loss rate of flame cleaning was effectively reduced.

[0074] As shown in Table 2, the alkalinity of the mold protection slag of Example 1 is slightly increased compared with that of Comparative Example 4, from 1.23 to 1.27. The increase in alkalinity is conducive to the formation of a crystalline phase in the solid slag film of the protection slag, the interface thermal resistance is increased, the glass body is reduced, and the radiation heat transfer is reduced, thereby achieving the purpose of slowing down the heat transfer; however, the increase in alkalinity is not large, and the increase in alkalinity is restricted by the lubrication of the ingot, because if the alkalinity is too high, the thickness of the liquid slag film will be reduced accordingly, and the lubrication of the ingot will be affected. At the same time, in order to avoid poor lubrication of the ingot caused by increasing the alkalinity, Example 1 reduces the viscosity of the protection slag to ensure the lubrication of the ingot and prevent the ingot from sticking or leaking. As the viscosity decreases, the slag consumption increases accordingly, so the melting rate of the protection slag is increased to ensure the slag consumption. The final results are shown in Table 3. Compared with Comparative Examples 4 and 6, the probability of corner cracks in the medium carbon steel slab prepared in Example 1 is reduced from 14% to 1.2%, which effectively reduces the corner cracks. The quality of the steel coil after rolling is tracked, and the results show that no repair occurs after the steel coil is rolled.

[0075] As shown in Table 1, the crystallizer vibration curve of Example 1 is controlled to be S=2+2V c , f=170-2V c , while the crystallizer vibration curve of comparative example 5 is controlled to be S=1.5+2V c , f=120-2V c Compared with Comparative Example 5, the negative sliding, positive sliding time, and oscillation mark spacing of Example 1 are significantly reduced. Since the negative sliding time can theoretically reduce the depth of the oscillation mark, the reduction of the oscillation mark depth and the reduction of the oscillation mark spacing are both important for reducing the transverse crack defects at the corners of the ingot. The final results are shown in Table 3. Compared with Comparative Example 5, the corner cracking and hot rolling spot peeling of the carbon steel slab in Example 1 are significantly lower than those in Comparative Example 5.

[0076] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A mold protection slag for reducing corner cracks in medium carbon steel slabs, characterized in that: It includes the following components by mass fraction: 30.05wt%-32.5wt% SiO2, 5.35wt%-5.55wt% Al2O3, 1.07wt%-0.87wt% Fe2O3, 37.39wt%-39.39wt% CaO, 4.21wt%-4.41wt% MgO, 0.16wt%-0.18wt% K2O, 0.7wt%-0.9wt% Li2O, 5.3wt%-5.5wt% Na2O, 0.02wt%-0.04wt% MnO, 1.52wt%-1.72wt% H2O, 7.96wt%-8.16wt% F, 4.55wt%-4.75wt% C.

2. The mold protection slag for reducing corner cracks in medium carbon steel slabs according to claim 1, characterized in that: The basicity of the mold protection slag is 1.17-1.37, and the melting rate at 1350°C is 26-28kg / (m 2 ·s), and the viscosity at 1300℃ is 0.113-0.133Pa·s.

3. A method for preparing a mold powder for reducing corner cracks in a medium carbon steel slab as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) weighing the raw materials of each component according to the ratio, mixing them evenly, adding water to the raw materials to mix, the mass ratio of the raw materials to water is 1:(1-2), wet grinding, and then sieving, the mesh size of the sieve is 0.1-1 mm, to obtain a slurry; (2) forming a granular protective slag by spray granulation; (3) Drying and screening the granular protective slag to obtain a finished product of the crystallizer protective slag, the drying temperature is 100-150° C., the drying time is 2-8 hours, and the particle size of the finished product of the crystallizer protective slag is 0.1-1 mm.

4. A method for preparing a medium carbon steel slab with reduced corner cracks, characterized in that: The use of a mold protection slag for reducing corner cracks in a medium carbon steel slab as claimed in claim 1 or 2 comprises the following steps: The medium carbon steel raw material is melted into molten steel, and the large ladle of molten steel is injected into the tundish through the long nozzle. The molten steel in the tundish flows into the crystallizer through the integral immersion nozzle. The crystallizer protective slag is added in advance to control the sinusoidal vibration curve of the crystallizer to be S=1+2V c , f=170-20V c , where S: stroke, mm; f: vibration frequency, min -1 ; V c : Pulling speed, m / min, control the cooling water volume of the wide surface of the crystallizer to 3900-4100L / min, and the cooling water volume of the narrow surface of the crystallizer to 370-390L / min. The molten steel gradually solidifies into a billet in the crystallizer, and then immerses it in the secondary cooling section for cooling to obtain a medium carbon steel slab.

5. A method for preparing a medium carbon steel slab with reduced corner cracks as claimed in claim 4, characterized in that: The drawing speed of the casting machine in the crystallizer is 0.9-1.5m / min.

6. A method for preparing a medium carbon steel slab with reduced corner cracks as claimed in claim 4, characterized in that: The negative sliding time of the crystallizer is 0.1540-0.1543s.

7. A method for preparing a medium carbon steel slab with reduced corner cracks as claimed in claim 4, characterized in that: The medium carbon steel grade is any one of Q235B, Q345XJ-H, A36-LB, CCS-A, and SS400.

8. A method for preparing a medium carbon steel slab with reduced corner cracks as claimed in claim 4, characterized in that: The dimensions of the crystallizer are 200-250 mm in thickness, 850-950 mm in length, and 1200-1300 mm in width.

9. A method for preparing a medium carbon steel slab with reduced corner cracks as claimed in claim 4, characterized in that: The inlet temperature of the crystallizer cooling water is 22-28℃.

10. A medium carbon steel slab prepared by the method for preparing a medium carbon steel slab with reduced corner cracks as described in any one of claims 4 to 9.